2022
DOI: 10.3389/fphys.2021.823013
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition Using Electroencephalography Signals of Older People for Reminiscence Therapy

Abstract: Objective: Numerous communication support systems based on reminiscence therapy have been developed. However, when using communication support systems, the emotional assessment of older people is generally conducted using verbal feedback or questionnaires. The purpose of this study is to investigate the feasibility of using Electroencephalography (EEG) signals for automatic emotion recognition during RT for older people.Participants: Eleven older people (mean 71.25, SD 4.66) and seven young people (mean 22.4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Our experiments were conducted on the dataset from the previous study ( Jiang et al, 2022 ). Eleven older adults (six males and five females) and seven younger adults (five males and two females) were randomly pair-matched into 11 groups, and each group engaged in 36 photo conversations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experiments were conducted on the dataset from the previous study ( Jiang et al, 2022 ). Eleven older adults (six males and five females) and seven younger adults (five males and two females) were randomly pair-matched into 11 groups, and each group engaged in 36 photo conversations.…”
Section: Methodsmentioning
confidence: 99%
“…Electroencephalogram signals used a 1–45 Hz bandpass filter (removal of the line interference) and a Chebyshev I high-pass filter to remove baseline drift ( Jiang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that the use of novel technologies for reminiscence therapy is more effective than traditional methods (Hayhurst, 2018). More recently, novel research has started to look into recognising emotional elicitation in older adults during reminiscence therapy using physiological signals; aiming to provide in-depth insights beyond PwDs' verbal feedback, which could lend a lens to therapy administers especially for PwD who face barriers with verbal communication (Jiang et al, 2022b(Jiang et al, , 2022d.…”
Section: Cognitive Assessment Training and Remeniscencementioning
confidence: 99%
“…Finally, difficulties in the areas of language and communication is a common symptom in PwD; it can be challenging for PwD to share their thoughts or express their emotions (Banovic et al, 2018). As such, it is imperative that tools, solutions, interventions, and technologies developed are based on sound human-centred principles, and sensitive to the needs of this population in a bid to design more user-friendly, highly engaging, and effective solutions (Tabbaa et al, 2020), which can also help PwD and those around them understand their emotions through means beyond verbal communication (Jiang et al, 2022a(Jiang et al, , 2022cTabbaa et al, 2021;Zeng et al, 2020aZeng et al, , 2020b.…”
Section: Introductionmentioning
confidence: 99%
“…An important biomedical link has been reported between RT and feeding; the former encourages persons with dementia to enjoy meals specific to the origin culture and remote experiences from their childhood, including participating in traditional related gastronomic events and involvement in cooking, using their tastes and customs, established before becoming mentally ill [10]. Moreover, through "electroencephalography (EEG) signals for automatic emotion recognition" one can see the objective effects of RT; in addition, "the pleasure level of RT and the (o. n.: eu-)stress level of the conversation is more conducive to the emotion classification of older people in the communication support systems" [193]. Hence, RT "can help improve communication, feelings of belonging..., mood, wellbeing", with beneficial intellective actions; further, with the aid of the impressive actual development and expansion of artificial intelligence (AI), there can be related digital progress: re-configuring RT in a customized paradigm, resembling the features provided by a human health professional (skilled/licensed carer or respectively, therapist), targeting thereby an "intangible cultural heritage", including "facial expression analysis and reinforcement learning techniques".…”
Section: Reminiscence Therapy (Rt)mentioning
confidence: 99%